BiSbTe‐Based Nanocomposites with High ZT: The Effect of SiC Nanodispersion on Thermoelectric Properties. (10th April 2013) - Li, Jianhui; Tan, Qing; Li, Jing‐Feng; Liu, Da‐Wei; Li, Fu; Li, Zong‐Yue; Zou, Minmin; Wang, Ke
Abstract Thermoelectric materials have potential applications in energy harvesting and electronic cooling devices, and bismuth antimony telluride (BiSbTe) alloys are the state‐of‐the‐art thermoelectric materials that have been widely used for several decades. It is demonstrated that mixing SiC nanoparticles into the BiSbTe matrix effectively enhances its thermoelectric properties; a high dimensionless figure of merit (ZT) value of up to 1.33 at 373 K is obtained in Bi0.3Sb1.7Te3 incorporated with only 0.4 vol% SiC nanoparticles. SiC nanoinclusions possessing coherent interfaces with the Bi0.3Sb1.7Te3 matrix can increase the Seebeck coefficient while increasing the electrical conductivity, in addition to its effect of reducing lattice thermal conductivity by enhancing phonon scattering. Nano‐SiC dispersion further endows the BiSbTe alloys with better mechanical properties, which are favorable for practical applications and device fabrication.